Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1136/bmjophth-2020-000458
|View full text |Cite
|
Sign up to set email alerts
|

Potential adverse effects of ciprofloxacin and tetracycline on ARPE-19 cell lines

Abstract: BackgroundWe aim to determine the possible adverse effects of ciprofloxacin (CPFX) and tetracycline (TETRA), as examples of bactericidal and bacteriostatic agents, respectively, on cultured human retinal pigment epithelial cells (ARPE-19).MethodsCells were treated with 30, 60 and 120 µg/mL of CPFX and TETRA. Cell metabolism was measured by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. JC-1 dye (5′,6,6′-tetrachloro-1,1′,3,3′-tetraethylbenzimidazolylcarbocyanine iodide) assay was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…The transition of JC-1 from red fluorescence to green fluorescence can easily detect the drop of cell membrane points, and the transition from red fluorescence to green fluorescence of JC-1 can also be used as an early detection indicator of apoptosis (Salimiaghdam et al. 2020 ). The results from JC-1 staining and western blot were consistent with flow cytometry ( Figure 4(C–F) ).…”
Section: Resultsmentioning
confidence: 99%
“…The transition of JC-1 from red fluorescence to green fluorescence can easily detect the drop of cell membrane points, and the transition from red fluorescence to green fluorescence of JC-1 can also be used as an early detection indicator of apoptosis (Salimiaghdam et al. 2020 ). The results from JC-1 staining and western blot were consistent with flow cytometry ( Figure 4(C–F) ).…”
Section: Resultsmentioning
confidence: 99%
“… 30 , 31 Interestingly, cultured human retinal pigment epithelium (RPE) cells treated with ciprofloxacin, a fluoroquinolone, displayed decreased viability with corresponding upregulation of inflammatory and pro-apoptotic genes. 32 This raises the possibility that fluoroquinolones exert a cytotoxic effect on RPE cells, thereby raising AMD risk. In a small prospective study of 76 patients who received oral fluoroquinolones and 50 sex-matched controls, Ozcelik-Kose et al 33 found that fluoroquinolones had no effect on retinal degeneration at one week and one month after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Besifloxacin, gatifloxacin, and moxifloxacin were exposed to human umbilical vein endothelial cells, resulting in a significant loss of cell viability after 24 h of exposure [65]. Clinically relevant concentrations of ciprofloxacin and tetracycline had detrimental impacts on human retinal pigment epithelial cell (ARPE-19 cell) lines in vitro, including the upregulation of genes related to apoptosis, inflammation, and the antioxidant pathways [66]. Antibacterial activity [70] Human retinal pigment epithelial cells…”
Section: In Vitro Studies On Fq Antibioticsmentioning
confidence: 99%